Play-based methods in teaching English - Demianenko, T. А. (My University, 2017)
Mastering English skills, especially grammar skills, has always been problematical for ESL students of any level. Having learned a lot of rules and done plenty of written exercises the students are not often able to apply them when speaking and don‟t identify them when listening. Furthermore, the grammar learning is perceived as effortful and boring work. Taking this problem into account a teacher should realize the barest necessity of rationalization of this kind of learning activity and the necessity of searching and practicing more efficient tools in teaching.
Keywords: developing language skills; play-based methods; educational games; efficient tools in teaching